The implementation of two stay two stray learning model to improve student discussion ability (Research, Society and Development, 2020)
This research has an aim to improve student learning process and ability of discussion through the learning model of Two Stay Two Stray. This research consider as Class Action Research. This research was conducted at State High school 1 which located in Kedaton Bandar, Bandar, Simalungun. This research was carried out from May to October 2019 which covered all activities from the preparation of proposals to the implementation of research. The implementations schedule in Accordance with English Language schedule. The result of this research showed that the entire aspect of discussion skill assessment has been improved much better in cycle III rather that in preliminary test. Cycle III has reach the determined target, which is 75% of student success to obtainscore ≥ 19. Based on the results of research and discussion that has been stated in the previous chapter, it can be concluded that discussion learning by Two Stay Two Stray learning model can help to improve discussion skills of Class X IPS-1 students at State Highschool I Bandar, Simalungun.